Combination of active methodologies to promote confidence in the preparation and defense of the bachelor’s dissertation. A study in the degree of finance and accounting - Albort-Morant, Gema; Masero-Moreno, Inmaculada Concepción; Montero-Benavides, Paula (Journal of Management and Business Education, 2022)
The teaching innovation developed in this research work proposes a combination of active teaching methodologies with the aim of improving the transversal competences necessary to successfully complete the Final Degree Project (FDP). Our study applies and combines three well-known active methodologies: Project-Oriented Learning, Inquiry-Based Learning and Collaborative Learning. These active methodologies are student-centered and are characterized by three fundamental features, participation, self-direction and self-learning. The first objective of this work is to present the experience of teaching innovation that has been developed in the field of the Degree in Finance and Accounting at the University of Seville, specifically, in the subject Banking Management, taught in the academic year 2021-2022. The second objective is to evaluate the results of the teaching innovation experience. For this purpose, the grades obtained in the different tasks developed under these methodologies were analyzed. The results obtained suggest a high level of satisfaction of the students who participated in the innovation experience. This, together with the grades obtained, leads us to positively value the combination of methodologies with respect to this objective and, therefore, to recognize its achievement. We believe that this proposal can serve as inspiration for methodological innovations aimed not only at developing active learning, but also at developing a more comprehensive preparation of students in relation to the development of the future FDP.